Determinants Of The VAT Gap In The European Union: An Empirical Evidence with Corruption Control As A Moderating Variable - Wijaya, Suparna; Surbakti, Sinarta Putra P. (WIM Solusi Prima, 2024)
The aim of this study was to determine the effect of Shadow Economy, Economic Growth, Trade Openness, and Corruption Control on VAT Gap. Additionally, this study aims to examine the moderating effect of Corruption Control on the relationship between independent variables and the dependent variable. The study was conducted using panel data regression with Panel-Corrected Standard Errors (PCSE) model in 25 European Union countries for the 2003-2020 period. The research findings indicate that all independent variables simultaneously have a significant impact on VAT Gap. Partially, Shadow Economy has a positive effect on VAT Gap, while Economic Growth has a negative effect on VAT Gap. However, Trade Openness and Corruption Control do not significantly affect VAT Gap. Corruption Control only moderates the relationship between Shadow Economy and VAT Gap negatively. This suggests that effective corruption control measures in EU countries can reduce the negative impact of Shadow Economy on VAT revenue. Based on this research, policymakers are expected to implement comprehensive monitoring and auditing practices, simplify business regulations, and enhance education and support to mitigate the potential loss of value-added tax (VAT).